2020
DOI: 10.1002/ecs2.3119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic origin on phenotypic divergence in Brook Trout populations stocked with domestic fish

Abstract: Phenotypic changes due to human activities are occurring at a far greater speed than those originating from natural causes in animal populations. For instance, phenotypic divergence among individuals may arise in populations supplemented with farm‐reared fish that are known to display different phenotypes from those of wild individuals because of domestication. Little is known about how these phenotypic differences are maintained when domestic and wild individuals face the same environment and hybridize, as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…Our results do not support these finding for our system s as we found no interactions between strain and temperature on survival, suggesting that the F1 Scott strain was as equally as sensitive as the F20+ Hill's strain under elevated temperatures (as well as current temperatures), and may not possess the requisite plasticity (in terms of thermal tolerance) when faced with this stressor. Recent research has shown that one generation in captivity is able to elicit phenotypic change resulting in no phenotypic differences between F1 and F>1 generations of captive fish (Farquharson, 2020;Gossieaux et al, 2020). Therefore, our results partially align with the findings of Fraser et al (2019), suggesting domestication (and unintentional selection for traits unsuitable to the wild) can possibly occur within one captive generation.…”
Section: Domestication and Egg-to-fry Survivalsupporting
confidence: 84%
“…Our results do not support these finding for our system s as we found no interactions between strain and temperature on survival, suggesting that the F1 Scott strain was as equally as sensitive as the F20+ Hill's strain under elevated temperatures (as well as current temperatures), and may not possess the requisite plasticity (in terms of thermal tolerance) when faced with this stressor. Recent research has shown that one generation in captivity is able to elicit phenotypic change resulting in no phenotypic differences between F1 and F>1 generations of captive fish (Farquharson, 2020;Gossieaux et al, 2020). Therefore, our results partially align with the findings of Fraser et al (2019), suggesting domestication (and unintentional selection for traits unsuitable to the wild) can possibly occur within one captive generation.…”
Section: Domestication and Egg-to-fry Survivalsupporting
confidence: 84%
“…Our results do not support these finding for our system s as we found no interactions between strain and temperature on survival, suggesting that the F 1 Scott strain was as equally as sensitive as the F 20+ Hill’s strain under elevated temperatures (as well as current temperatures), and may not possess the requisite plasticity (in terms of thermal tolerance) when faced with this stressor. Recent research has shown that one generation in captivity is able to elicit phenotypic change resulting in no phenotypic differences between F 1 and F >1 generations of captive fish (Farquharson, 2020; Gossieaux et al, 2020). Therefore, our results partially align with the findings of Fraser et al (2019), suggesting domestication (and unintentional selection for traits unsuitable to the wild) can possibly occur within one captive generation.…”
Section: Discussionmentioning
confidence: 99%
“…With concerns for the effects stocked fishes have on the production in natural systems (Einum & Fleming, 2001; Ersbak & Haase, 1983; Gossieaux et al, 2020; Kostow, 2004), characterizing the implications of warming water temperatures on the survival and quality of stocked fish both in hatchery settings, the wild, and with varying generations spent in captivity (as our study addressed), is imperative for predicting the success of such programs (Einum & Fleming, 2001; O’Sullivan et al, 2020; Venditti et al, 2018). As with other studies (Acornley, 1999; Beacham & Murray, 1985; Bellinger et al, 2018; Chezik et al, 2014; Cingi et al, 2010; Marten, 1992; Molony et al, 2004; T.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the hatchery environment can elicit phenotypic and genetic changes which can be maladapted for survival in the wild (e.g., Heath et al 2003;Sundström et al 2004;Le Luyer et al 2017). As a result, genetic introgression between hatchery and wild stocks may negatively affect fitness, resiliency, and adaptive potential via the disruption of co-adapted gene complexes (Hallerman 2003;Naish et al 2007), introduction of maladaptive phenotypes (Bolstad et al 2017;Gossieaux et al 2020) or deleterious mutations (Ferchaud et al 2018), and increased susceptibility to disease (Currens et al 1997).…”
Section: Introductionmentioning
confidence: 99%